ANALISIS PENILAIAN PENGUATAN PENDIDIKAN KARAKTER DI SD NEGERI 69 BANDA ACEH - Helminsyah; Aprian Subhananto; Sopi Yana (Program Studi Pendidikan Guru Sekolah Dasar, 2019)
Education is a tool that serves to improve the human beings both from the aspect of ability and personality, therefore in education should be input strengthening the character education.The importance of strengthening the character rating is based on the reason that there are now many deviant behaviors contrary to existing norms, hence the study titled: Strengthening of Character education assessment in elementary School 69 Banda Aceh.The purpose of this research is to describe the strengthening of character education in class IV of SDN 69 Banda Aceh.This type of research is qualitative descriptive research. The subject in this study was all teachers in Elementary School 69 Banda Aceh, amounting to 16 people.The data collection techniques used in this study are, by using polls, interviews and documentation. The results of this study showed that: the implementation of character education strengthening in SDN 69 Banda Aceh is very good with the program implementation rate of 84.77% which consist of. (1) Planning Character Education Strengthening program with the level of implementation reached 84.50% from the indicator of the presence of trengthening character education development team, program trengthening character education preparation process, management of trengthening character education program time, and success indicators and Carrying Capacity (2) Implementation of trengthening character education program in SDN 69 Banda Aceh with a level of reliability reached 85.36% from the indicator of the implementation of the trengthening character education program and the strategy of implementation of trengthening character education program of eaching and learning activities, extracurricular, and Learning through school culture (3) evaluation of the character education strengthening program in SDN 69 Banda Aceh with a level of reliability reached 84.45% from the indicator of the evaluation team of trengthening character education program, evaluation process (preparation of Successful assessment of trengthening character education program, data retrieval and processing, evaluation result, and school follow-up from trengthening character educatioprogram evaluation.The implementation category of trengthening character education program implemented in Elementary School 69 is very good. Abstrak Pendidikan merupakan sarana yang berfungsi untuk memperbaikikuliatas manusia baik dari aspek kemampuan maupun kepribadian maka dari itu dalam pendidikan perlu dimasukan penguatan pendidikan karakter. Pentingnya penguatan penilaian karakter didasarkan pada alasan bahwa sekarang banyak terjadi perilaku menyimpang yang bertentangan dengan norma yang ada, maka dari itu penelitian ini berjudul: Analisis Penilaian Penguatan Pendidikan Karakter di SD Negeri 69 Banda Aceh. Tujuan dari penelitian ini adalah Untuk mendeskripsikan penguatan pendidikan karakter di kelas IV SDN 69 Banda Aceh. Jenis penelitian ini adalah penelitian kualitatif deskriptif. Subjek dalam penelitian ini adalah seluruh guru yang ada di sekolah SDN 69 Banda Aceh yang berjumlah 16 orang. Teknik pengumpulan data yang digunakan dalam penelitian ini yaitu, dengan menggunakan angket, wawancara dan dokumentasi. Hasil penelitian ini menunjukkan bahwa: pelaksanaan penguatan pendidikan karakter di SDN 69 Banda Aceh tergolong sangat baik dengan tingkat keterlaksanaan program mencapai 84,77% yang terdiri dari (1) perencanaan program penguatan pendidikan karakter dengan tingkat keterlaksanaan mencapai 84,50 % yang didapatkan dari indikator adanya tim pengembang penguatan pendidikan karakter, proses penyusunan program PPK, pengelolaan waktu program PPK, dan indikator keberhasilan serta daya dukung (2) pelaksanaan program penguatan pendidikan karakter di SDN 69 Banda Aceh dengan tingkat keterlaksanaan mencapai 85,36 % yang didapatkan dari indikator adanya pedoman pelaksanaan program penguatan pendidikan karakter dan strategi pelaksanaan program penguatan pendidikan karakter yaitu proses Kegiatan Belajar Mengajar, ekstrakurikuler, dan pembiasaan melalui budaya sekolah (3) evaluasi program penguatan pendidikan karakter di SDN 69 Banda Aceh dengan tingkat keterlaksanaan mencapai 84,45 % yang didapatkan dari indikator adanya tim evaluasi program penguatan pendidikan karakter , proses evaluasi (penyusunan instrumen penilaian keberhasilan program penguatan pendidikan karakter , pengambilan dan pengolahan data, penyimpulan hasil evaluasi), dan tindak lanjut sekolah dari hasil evaluasi program penguatan pendidikan karakter. Kategori keterlaksanaan program penguatan pendidikan karakter yang dilaksanakan pada sekolah SD Negeri 69 tersebut sangat baik. Kata Kunci: Penilaian, Pendidikan Karakter